ANALISIS BOBOT KOMPONEN WAKTU PADA PERJALANAN MENGGUNAKAN ANGKUTAN UMUM PERKOTAAN - Risdiyanto, Risdiyanto; Putri, Adelia Berliani Harnanto; Kresnanto, Nindyo Cahyo (Jurnal Riset Rekayasa Sipil, 2023)
Traffic congestion is a serious problem in many cities in the world. Congestion will be reduced if most private vehicle users want to switch to using Urban Public Transport (AUP) when traveling. In order for AUP to be in demand, AUP services must be better. One of the most important services in attracting AUP passengers is the short travel time. The intended travel time is a combination of time to the stop, waiting time at the stop, time in the vehicle, transfer time, and travel time from the stop to the final destination. In order for travel time to be calculated, the weight of each component of travel time must be known. The purpose of this study was to determine the weight of each type of travel time component by taking the case of the Trans Jogja Bus (BTJ). The analysis was carried out using the Analytical Hierarchy Process (AHP) method. Data were obtained by conducting interviews / distributing questionnaires both in person and online, to 103 young respondents in urban Yogyakarta. Based on the results of the study, it was found that the components of travel time with weights from the largest in succession were waiting time at the bus stop, followed by time to the bus stop, transfer time, time from the bus stop to the final destination, and time in the vehicle. These results indicate that reducing waiting time at bus stops is a priority program that needs to be done to shorten the total travel time so that AUP becomes attractive.